Uji Aktivitas Antijamur Minyak Atsiri Bawang Bombay ( Allium cepa L.) terhadap Pseudomonas aeruginosa - Miftahur Rahmi (Jurnal Penelitian Farmasi Indonesia, 2019)
Onions (Allium cepa L) contain essential oils which contain sulfur in the form of isothiocyanates or thiosulfinates which are known as antibacterial and antifungal. The aims of this study was to determine the antibacterial activity and minimum inhibitory concentration (MIC)of essential oils from onions (Allium cepa L) against Pseudomonas aeruginosa. This research was an experimental study using the Kirby-bauer method using discs. The results were obtained by concentration of 20%(C1), 10%(C2), 5%(C3), 2,5%(C4), 1,25%(C5), 0,625%(C6), and 0,312%(C7) provide the inhibition with an average diameter are 14,94 mm, 14,17 mm, 13,62 mm, 12,97 mm, 11,97 mm, 9,11 mm and 0 mm. From this research it can be concluded that essential oils from onions (Allium cepa L) can inhibit the growth of Pseudomonas aeruginosaand the minimum inhibitory concentration (MIC) of essential oils from onions (Allium cepa L) against Pseudomonas aeruginosawas at a concentration of 0,612% (C6) with an average diameter of 9,11 mm.